61.0k views
2 votes

f(x) = (3(x-1)(x+1))/((x-3)(x+3))

Domain:
V.A:
Roots:
Y-int:
H.A:
Holes:
O.A:

Also, draw on the graph attached.

f(x) = (3(x-1)(x+1))/((x-3)(x+3)) Domain: V.A: Roots: Y-int: H.A: Holes: O.A: Also-example-1
User Bylijinnan
by
4.7k points

1 Answer

4 votes

QUESTION 1

i) The given function is


f(x)=(3(x-1)(x+1))/((x-3)(x+3))

The domain is


(x-3)(x+3)\\e0


(x-3)\\e0,(x+3)\\e0


x\\e3,x\\e-3

ii) To find the vertical asymptote equate the denminator to zero.


(x-3)(x+3)\=0


(x-3)=0,(x+3)=0


x=3,x=-3

iii) To find the roots equate the numerator zero.


3(x-1)(x+1)=0


3(x-1)=0,(x+1)=0


(x-1)=0, (x+1)=0


x=1, x=-1

iv) To find the y-intercept substitute
x=0 into the function;


f(0)=(3(0-1)(0+1))/((0-3)(0+3))


f(0)=(-3)/((-3)(3))


f(0)=(1)/(3)

The y-intercept is
(1)/(3)

v) The horizontal asymptote is given by


lim_(x\to \infty)(3(x-1)(x+1))/((x-3)(x+3))=3

The horizontal asymptote is y=3

vi) The rational function has no common linear factor.

This rational function has no holes.

vii) This rational function is a proper function. It has no oblique asymptote.

f(x) = (3(x-1)(x+1))/((x-3)(x+3)) Domain: V.A: Roots: Y-int: H.A: Holes: O.A: Also-example-1
User Puelo
by
5.2k points